A nélkülözjetetlen eszközök értelmezése és a postai szolgáltatások - Pál Valentiny; Károly Miklós Kiss (Hungarian Academy of Sciences, Institute of Economics, 2009)
– The existence and the use of the essential facilities doctrine was questioned in theory and in practice. Although the doctrine was developed in antitrust, it became a frequently cited notion in the regulation of network utilities. Its relevance is hotly debated during the setup of the new regulatory framework for newly liberalized postal services. This paper highlights the emergence and evolution of different interpretations of the doctrine in the US. We then explore the various use of the doctrine in competition polcy and regulation in the EU and Hungary. The next section is devoted to the controversies around the essential facility doctrine in the postal sector. Finally we provide some concluding remarks.
Keywords: K21; L4; L51; L87; 330; essential facilities; competition policy; regulation; postal services; Kartellrecht; Wettbewerbspolitik; Regulierung; Postsektor; USA; EU-Staaten